A Systematic Review on the Impact of Helicobacter Pylori Eradication on Gastrointestinal and Extra-Gastrointestinal Diseases - Majid Shah, Brekhna Shah, Kashmala Shah, Safa Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Helicobacter pylori (H. pylori) is a major cause of peptic ulcer disease (PUD) and gastric cancer, with emerging associations with metabolic, cardiovascular, neurological, and autoimmune diseases. This systematic review evaluates the impact of H. pylori infection and its eradication on these conditions. Methods: A systematic search was conducted across different databases from January 2000 to June 2023. Eligible studies included clinical trials, cohort studies, and meta-analyses that assessed disease progression or symptom improvement post-eradication. Results: Eradication significantly reduces PUD recurrence (from 85.3% to 6.8%) and lowers gastric cancer risk by 36%, though its effect on intestinal metaplasia remains unclear. The impact on GERD is inconclusive. H. pylori increases insulin resistance by 54% and metabolic syndrome risk by 31%, with eradication improving lipid profiles and glucose metabolism. The infection is linked to atherosclerosis, hypertension, and systemic inflammation, with eradication reducing CIMT and inflammatory markers. H. pylori is also associated with Alzheimer’s and Parkinson’s diseases, likely via gut-brain axis disruption, and may impair levodopa absorption in Parkinson’s disease. Autoimmune links include rheumatoid arthritis and Hashimoto’s thyroiditis through molecular mimicry and immune activation. Conclusion: While eradication is essential for GI diseases, its role in extra-GI conditions remains under investigation. Targeted eradication in high-risk populations may offer therapeutic benefits, but broad eradication requires further study. Keywords: Helicobacter pylori, peptic ulcer, gastric cancer, metabolic syndrome, cardiovascular disease, neurodegenerative disorders, autoimmune diseases, eradication therapy.